Biological microparticles in the Hans Tausen Ice Cap, North Greenland - Gruber, Sabine; Jaenicke, Ruprecht (Meddelelser om Grønland. Geoscience, 2001)
Samples from three different depths in the Hans Tausen ice core (82.5°N, 37.5°W) in Peary Land, North Greenland were examined. The aim was to determine the size distributions of the total and biological particles in the size range 0.2 μm < radius < 41.2 μm. To date, the concentration of the whole spectrum of biological microparticles including viruses, bacteria, spores, pollen, plant debris and animal fragments in ice is still unknown. Biological particles were distinguished from non-biological ones by single particle analysis. The mean concentration of the total insoluble particles in ice was 1.02E+05 per ml, of these, 3.20% were biological.